Охридската архиепископија во времето на Лионската унија (1274-1280) - Nedeski, Viktor (Православен богословски факултет „Св. Климент Охридски“ Скопје, 2019)
The Ohrid Archbishopric headed by Archbishop Theodore Kerameas in 1274 accepted the Union of Lyons, and the official church of Ohrid remained faithful to the Union until its collapse. The election of Gennadius for the Ohrid throne after Theodore Kerameas is quite a logical historical fact. This provides a historically well-grounded resolution of the events in Ohrid that are thus set in line with the global church mood in the Byzantine Empire in the second half of the 13th century.